THE LEGAL AND POLITICS BASES OF NATIONAL SECURTY OF RUSSIA: INTERNATIONAL ASPECT - N. P. Medvedev; S. N. Ivakhnenko (Современная наука и инновации)
The article raises the problem of creating a new international legal doctrine, taking into account the current realities, the realities, without which today it is impossible to talk about national security and civilised international law.